2019
DOI: 10.1037/pas0000696
|View full text |Cite
|
Sign up to set email alerts
|

Comparability of self- and other-rated personality structure.

Abstract: It is commonly accepted that gathering information via multiple assessment methods (e.g., interview and questionnaire, self-and informant report) is important for establishing construct validity. Although numerous articles report convergent and discriminant agreement correlations between self-and other ratings of personality, studies of the structure of personality from such ratings are less common. The present study addresses this gap using a meta-analytic data set (N range ϭ 157-9,295) of various versions (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…While some research suggests that close others may be just as accurate as focal raters at rating common daily activities (Vazire & Mehl, 2008), this did not appear to be the case for problematic smartphone use. These results are consistent with theories (Funder, 1995;Nuzum et al, 2019) that validity and self-other agreement is directly related to the amount of relevant information possessed by the rater (Connelly & Ones, 2010;Vazire & Mehl, 2008). In the case of problematic smartphone use, there is the extent to which a rater is able to observe a person's smartphone use in a variety of contexts and situations over time.…”
Section: Self-and Other-ratings Of Problematic Smartphone Usesupporting
confidence: 86%
See 1 more Smart Citation
“…While some research suggests that close others may be just as accurate as focal raters at rating common daily activities (Vazire & Mehl, 2008), this did not appear to be the case for problematic smartphone use. These results are consistent with theories (Funder, 1995;Nuzum et al, 2019) that validity and self-other agreement is directly related to the amount of relevant information possessed by the rater (Connelly & Ones, 2010;Vazire & Mehl, 2008). In the case of problematic smartphone use, there is the extent to which a rater is able to observe a person's smartphone use in a variety of contexts and situations over time.…”
Section: Self-and Other-ratings Of Problematic Smartphone Usesupporting
confidence: 86%
“…Although studies examining other constructs have found reasonable self-other agreement in the field of personality (e.g. H. Kim, Di Domenico, & Connelly, 2019;Nuzum, Ready, & Clark, 2019), and that other-ratings can add unique explanatory information to an assessment of a focal (Tornow, 1993), there are conditions that can enhance or degrade the quality of other-ratings. Valid other-ratings require that the focal behaves in a consistent manner across situations where trait perceptions might be formed (Kenrick & Funder, 1988), and, other-raters must be able to accurately judge the observed behavior (Bernieri, Zuckerman, Koestner, & Rosenthal, 1994).…”
Section: Self-and Other-ratings Of Problematic Smartphone Usementioning
confidence: 99%
“…Because personality dysfunction is essentially relational in its nature and, thus, interactive in its appearance, the symptoms may not be apparent to or acknowledged by the person with the disorder. In any case, research suggests that some traits converge more strongly than others in terms of self versus other ratings (Connelly & Ones, 2010; Kelley, Edens, & Morey, 2017; McDonald, 2008; Nuzum, Ready, & Clark, 2019). Additionally, informant-report measures have been found to be more externally valid especially for criteria of social nature and functioning as well as more accurate when describing traits that are best observed by others (Connelly & Ones, 2010).…”
Section: Rationale For Exploring Clinician-reported Icd-11 Trait Doma...mentioning
confidence: 99%
“…To date, a number of studies have already investigated associations between self-reported ICD-11 trait domains and traditional PD types (Bach et al, 2018; Bach, Kerber, et al, 2020; Fang et al, 2021; García et al, 2022; Kim et al, 2021; Lugo et al, 2019; Sellbom et al, 2020; Sellbom et al, in press; Simon et al, 2023; Sorrel et al, 2022), which overall showed expected and conceptually coherent associations. However, associations have not yet been investigated with respect to clinician ratings performed by practitioners, which is deemed important because self-report bias seems to increase by the severity of personality pathology (e.g., Nuzum et al, 2019). Moreover, clinical practitioners are those who eventually will be using the new diagnostic approach, and clinician ratings therefore seem most relevant for routine clinical practice.…”
Section: International Classification Of Diseases (11th Edition; Icd-...mentioning
confidence: 99%